The influence of academic library staff body language on library users during initialization and negotiation - Paule, Dominique C. (2002)
This study concerned itself with three main areas regarding body language and the role that it plays in the communication process that takes place within the library framework. Primarily, the study examined whether library users are affected by academic library staff (ALS) body language such that they become hesitant to approach them and/or uneasy while interacting with them. In cases where library users do become hesitant to approach and/or uneasy to interact because of ALS body language, the study examined to what degree are the library users affected. Lastly, the study attempted to clarify the aforementioned influence of ALS body language by examining whether the gender or age of library users intervene in the way they are affected by ALS body language.